Nucleophilic substitution of α-haloenones with phenols. Issue 13 (1st April 2015) - Mareev, Alexander V.; Ushakov, Igor A.; Rulev, Alexander Yu.
Abstract: The α-haloenones undergo cine -substitution upon reaction with phenolic reagents under basic conditions. A convenient method for the synthesis of push–pull aroxyenones was developed based on this reaction. Graphical abstract: